Convergence Analysis of Economic Growth in East Java - Amalia, Sri Karima; Santoso, Dwi Budi; Sasongko, Sasongko (Universitas Negeri Semarang, 2018)
Convergence and divergence of economic growth is a regional economic issue. The concept of convergence occurs when areas with poor economies tend to grow faster than areas with a rich economy whereas divergence occurs otherwise.Ã‚Â East Java has a high economic growth but has a high inequality between districts/municipalities as well.Ã‚Â Based on the concept of the inverted U-shape of the Kuznets curve, the East Java situation thus indicates that East Java is at the starting point of economic development. Therefore, it is necessary to develop high economic growth with low inequality through acceleration of convergence by knowing the level of convergence of economic growth and acceleration factors of economic growth convergence of East Java. This study uses panel data from 38 districts/municipalities in East Java between 2005 and 2014 by adopting the model Barro & Sala-i-Martin (1992) then the model specification in answering research objectives are sigma convergence, absolute convergence, and conditional convergence. The estimation results show that in East Java economic growth is convergent at a low level so that efforts need to accelerate the convergence that can be reached through 5 (five) development policies, (i) equalization of basic infrastructure such as access equity (ii) equal distribution of energy availability, (iii) equalization of investment, (iv) equal distribution of labor force, and (v) equality of labor productivity